Marek's Disease in Chicken: Clinico-Pathological Aspect and Diagnosis - Rini Damayanti; Helmy Hamid (Indonesian Center for Animal Research and Development, 2002)
Marek’s is a limphoproliferative and oncogenic disease of poultry caused by a serotype 1 herpesvirus. Chicken between 10 and 15 weeks of age are the most susceptible although in some outbreaks it also affects other ages. The causal agent consists of some virus strains with different pathotypes causing a variety of clinical and pathological manifestations. The main pathological features are neurological lesion and lymphoma formation in some visceral organs. Marek’s disease is clinically classified as classical, acute, peracute and chronic with neurological disorder and superficial tumor. At necropsy the peripheral nerves were enlarged, discoloured and loss of striation. There were formation of lymphoid tumour in various visceral organs. Microscopically Marek’s produced non suppurative encephalitis/neuritis and pleomorphic tumour. The diagnosis is based on the history of the disease, age of affected chicken, clinical and pathological features. A definitive diagnosis is made by virological and serological tests. Some of the Marek’s cases in Indonesia were discussed in this paper, as well as review on clinico- pathological aspects how to confirm the diagnosis of Marek’s. Key words. Marek’s Disease, chicken, clinical, pathological, diagnosis